2009
DOI: 10.1177/1465116509346782
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Interest Group Influence Using Quantitative Text Analysis

Abstract: The analysis of interest group influence is crucial in order to explain policy outcomes and to assess the democratic legitimacy of the European Union. However, owing to methodological difficulties in operationalizing influence, only few have studied it. This article therefore proposes a new approach to the measurement of influence, drawing on quantitative text analysis. By comparing interest groups’ policy positions with the final policy output, one can draw conclusions about the winners and losers of the deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
147
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(155 citation statements)
references
References 15 publications
1
147
0
7
Order By: Relevance
“…Alternatively, content analysis may allow verifying whether interest-group positions/statements find their way into 'their' politicians' speeches, enquiries, bills, or policy initiatives. Such content-analytical approaches recently have been fruitfully applied to measure interest-group influence on European Union policy-making (e.g., Klüver 2009). An alternative empirical strategy is to examine the behaviour of moonlighting politicians using roll-call votes or minutes of committee meetings which affect the organisations linked to these politicians.…”
Section: Public Versus Private Interests: Empirical Evidencementioning
confidence: 99%
“…Alternatively, content analysis may allow verifying whether interest-group positions/statements find their way into 'their' politicians' speeches, enquiries, bills, or policy initiatives. Such content-analytical approaches recently have been fruitfully applied to measure interest-group influence on European Union policy-making (e.g., Klüver 2009). An alternative empirical strategy is to examine the behaviour of moonlighting politicians using roll-call votes or minutes of committee meetings which affect the organisations linked to these politicians.…”
Section: Public Versus Private Interests: Empirical Evidencementioning
confidence: 99%
“…It assumes that a government is determined to implement the preferred policies of its voters irrespective of opposition from various powerful actors in the society. Previous research has demonstrated that governments are not immune against pressures from interest groups and especially not against pressure from powerful business entrepreneurs (Golden 1998;Klüver 2009;Yackee and Yackee 2006). A remarkable example for the significant influence of interest groups on policy outcomes is the lobbying of the National Rifle Association in the US against gun control which is successful against the majority's preference for a more restricted gun control (Dearden 2015).…”
Section: 3) Critical Discussion Of David Bearce's 'Party-as-agent Mmentioning
confidence: 99%
“…His conceptualisation of the EU policy process from a framing lens produces relevant insights that supplement traditional EU research which is much more focused on formal institutional analysis. Since his 2009 publication, the experience of Daviter's empirical exercises was adopted and further refined in some other studies (Klüver, 2009;Boräng et al, 2014;Eising et al, 2015).…”
Section: A U T H O R C O P Ymentioning
confidence: 99%